PERANAN KOPERASI DALAM MENUNJANG KINERJA PETANI KOPI - Wini Fetia Wardhani dan Karya (Program Studi Agroteknologi Faperta UNIBBA, 2021)
The role of cooperatives in developing and utilizing the resources found in the surrounding area is expected to have a positive impact in advancing the empowerment of residents who need cooperatives as facilitators to support activities carried out. In this case, several obstacles faced by business actors, especially in the regions, namely capital, marketing and production techniques. One of the cooperatives that is currently growing rapidly is the coffee farmer cooperative, especially in West Java and generally in Indonesia. This is evidenced by the existence of several coffee farmer cooperatives in the West Java area and they have been managed very well. The purpose of the study was to determine the participation of cooperative members in helping the performance. In this study the method used is a mixed method that combines qualitative and quantitative methods. Mixed methods research is a research method that involves the use of e-methods, namely qualitative research and quantitative methods in a single study or one study. The results of the study indicate that it is necessary to conduct research and analysis on how much influence information technology has and also the participation of all members in advancing their respective cooperatives. In this case, cooperatives also need people who are competent and can work well in order to assist cooperative members in implementing the information technology.